Characterizing Lung Particulates Using Quantitative Microscopy in Coal Miners With Severe Pneumoconiosis. - Hua, Jeremy T.; Cool, Carlyne D.; Lowers, Heather A.; Go, Leonard H. T.; Zell-Baran, Lauren M.; Sarver, Emily A.; Almberg, Kirsten S.; Pang, Kathy D.; Majka, Susan M.; Franko, Angela D.; Vorajee, Naseema I.; Cohen, Robert A.; et al. (Archives of Pathology & Laboratory Medicine, 2024)
Context.--Current approaches for characterizing retained lung dust using pathologists' qualitative assessment or scanning electron microscopy with energy-dispersive spectroscopy (SEM/EDS) have limitations. Objective.--To explore polarized light microscopy coupled with image-processing software, termed quantitative microscopy-particulate matter (QM-PM), as a tool to characterize in situ dust in lung tissue of US coal miners with progressive massive fibrosis. Design.--We developed a standardized protocol using microscopy images to characterize the in situ burden of birefringent crystalline silica/silicate particles (mineral density) and carbonaceous particles (pigment fraction). Mineral density and pigment fraction were compared with pathologists' qualitative assessments and SEM/EDS analyses. Particle features were compared between historical (born before 1930) and contemporary coal miners, who likely had different exposures following changes in mining technology. Results.--Lung tissue samples from 85 coal miners (62 historical and 23 contemporary) and 10 healthy controls were analyzed using QM-PM. Mineral density and pigment fraction measurements with QM-PM were comparable to consensus pathologists' scoring and SEM/EDS analyses. Contemporary miners had greater mineral density than historical miners (186 456 versus 63 727/mm³; P = .02) and controls (4542/mm³), consistent with higher amounts of silica/silicate dust. Contemporary and historical miners had similar particle sizes (median area, 1.00 versus 1.14 µm² P = .46) and birefringence under polarized light (median grayscale brightness: 80.9 versus 87.6; P = .29). Conclusions.--QM-PM reliably characterizes in situ silica/silicate and carbonaceous particles in a reproducible, automated, accessible, and time/cost/labor-efficient manner, and shows promise as a tool for understanding occupational lung pathology and targeting exposure controls.